My Atlas. - Flusser, Vilém (Flusser Studies, 2012)
The author discusses about atlases. He examines the changes in atlases by reflecting how atlases were used during his grandfather's time and the present. He outlines how atlases began to spread in different directions. He states that atlases became colourful, and began to zoom closer to the earth's surface. He also mentions that the atlases began to integrate history and people into geography.